PENGARUH PENERAPAN LKS FISIKA BERBASIS MODEL PEMBELAJARAN NOVICK TERHADAP HASIL BELAJAR SISWA KELAS VIII SMP N 8 PADANG - Stavinibelia Stavinibelia (PILLAR OF PHYSICS EDUCATION, 2014)
This research is backgrounded by the minimal using of instructional materials that give opportunity for the students to learn from the real experience and find the concept of physics by themself. This study aim to look at the effect of the application of physics’s student worksheet (LKS) based on Novick learning model for learning achievement of eighth grade students of SMP N 8 Padang. The population quasi-experimental with randomized control group only design is all eighth grade students of SMP N 8 Padang. The sampling technique was done by purposive sampling. Analysis using t-test at 0,05 significance level for cognitive, affective, and psychomotor learning achievement. The results showed that application of physics’s student worksheet based Novick learning model in learning to influential the learning achievement of students class VIII SMP N 8 Padang.